T-G-A Deficiency Pattern in Protein-Coding Genes and Its Potential Reason - Jin, Yan-Ting; Pu, Dong-Kai; Guo, Hai-Xia; Deng, Zixin; Chen, Ling-Ling; Guo, Feng-Biao (Frontiers in Microbiology, 2022)
If a stop codon appears within one gene then its translation will be terminated earlier than expected. False folding of premature protein will be adverse to the host and hence all functional genes would tend to avoid intragenic stop codons. Therefore, we hypothesize that there will be less frequency of nucleotides corresponding to stop codons at each codon position of genes. Here we validate this inference by investigating nucleotide frequency at large scale and results from 19911 prokaryotes genomes revealed that nucleotide coinciding with stop codons indeed have the lowest frequency in most genomes. Interestingly, genes with three types of stop codons all tend to follow T-G-A deficiency pattern, suggesting that the property of avoiding intragenic termination pressure is the same and the major stop codon TGA plays dominant role on this effect. Finally, a positive correlation between TGA deficiency extent and base length was observed in start-experimentally verified genes of E. coli. This strengthens proof of our hypothesis. The T-G-A deficiency pattern observed would help to understand the evolution of codon usage tactics in extant organisms.